Painel IV - O projeto da nova lei de defesa da concorrência - Bruna, Sergio; Belliboni, Flavio; Coelho, Tulio; Dutra, Pedro; Goldberg, Daniel (Revista do IBRAC, 2024)
Sergio Bruna .................... 233 Flavio Belliboni .................... 233 Tulio Coelho .................... 240 Pedro Dutra .................... 248 Daniel Goldberg ..................... 255 DEBATE .................... 272